CORRELATION OF NUTRITIONAL STATE AND PHYSICAL ACTIVITY LEVEL IN ADULT INDIVIDUALS OF THE VALE DO SINOS REGION, RIO GRANDE DO SUL STATE, BRAZIL (Fiep Bulletin - online, 2014)
This paper aims at relating the nutritional state with the physical activity level of adult individuals of the Vale do Sinos Region, Rio Grande do Sul State, Brazil. In this descriptive study with 965 subjects from 18 to 80 years old, selected through convenience, the subjects were submitted to the short version of the International Physical Activity Questionnaire and to the 24h food inquiry for the identification of the eating habits and macronutrients intake, calculated using the professional version of the dietWin® software. The Body Mass Index (BMI) was applied for the evaluation of the nutritional state, with the use of a scale and a stadiometer for variable height. The data was statistically analyzed through ANOVA and Pearson correlation. The results pointed to the following classification: 38.6% eutrophic, 39.6% overweight and 39.3% obese. As to the level of physical activity, the subjects were classified as insufficiently active (IA), sufficiently active (SA) and very active (VA). A strong relation (p
Keywords: Eating control; Physical activity; Healthy habits